A proposed collaborative framework by using artificial intelligence-internet of things (AI-IoT) in COVID-19 pandemic situation for healthcare workers. (1st October 2020) - Kumar, Shashank; Raut, Rakesh D.; Narkhede, Balkrishna E.
ABSTRACT: The COVID-19 epidemic has created a global fear for humanity. Despite technological advancement, the use of face masks, hand gloves, and sanitizers are the only available preventives measures to stop the spread and transmission of coronavirus. Healthcare providers and medical staffs are always at risk of infection as they deal with the infected person at the frontline. The safety of health care workers is essential as the number of infected health care works is increasing day by day. A detailed literature review is done on a previous epidemic outbreak and COVID-19 by using suitable keywords on SCOPUS. During the analysis of literature, several challenges were found that restrict the operation of the health care workers and cause safety issues for them. This research paper aims to identify the challenges faced by healthcare sectors in dealing with this epidemic outbreak and to propose the potential solutions in terms of popular technologies like AI and IoT by doing a critical analysis of literature. The study contributes by identifying the issues and categorizing them into physical, operational, resource-based, organizational, technological, and external health care challenges. Further, suggestions and future research direction concerning epidemic control are explained for practitioners and academicians.